Clinical, radiologic, and genetic characteristics of histone H3 K27M-mutant diffuse midline gliomas in adults. Issue 1 (22nd October 2020) - Schulte, Jessica D; Buerki, Robin A; Lapointe, Sarah; Molinaro, Annette M; Zhang, Yalan; Villanueva-Meyer, Javier E; Perry, Arie; Phillips, Joanna J; Tihan, Tarik; Bollen, Andrew W; Pekmezci, Melike; Butowski, Nicholas; et al.
Abstract: Background: "Diffuse midline glioma (DMG), H3 K27M-mutant" is a new tumor entity established in the 2016 WHO classification of Tumors of the Central Nervous System that comprises a set of diffuse gliomas arising in midline structures and is molecularly defined by a K27M mutation in genes encoding the histone 3 variants H3.3 or H3.1. While this tumor entity is associated with poor prognosis in children, clinical experience in adults remains limited. Methods: Patient demographics, radiologic and pathologic characteristics, treatment course, progression, and patient survival were collected for 60 adult patients with DMG, H3 K27M-mutant. A subset of tumors also underwent next-generation sequencing. Analysis of progression-free survival and overall survival was conducted using Kaplan–Meier modeling, and univariate and multivariate analysis. Results: Median patient age was 32 years (range 18–71 years). Tumors were centered in the thalamus ( n = 34), spinal cord (10), brainstem (5), cerebellum (4), or other midline sites (4), or were multifocal (3). Genomic profiling revealed p.K27M mutations exclusively in the H3F3A gene and an absence of mutations in HIST1H3B or HIST1H3C, which are present in approximately one-third of pediatric DMGs. Accompanying mutations in TP53, PPM1D, FGFR1, NF1, and ATRX were frequently found. The overall survival of this adult cohort was 27.6 months, longer than historical averages for both H3 K27M-mutant DMG in children and IDH-wildtype glioblastoma in adults. Conclusions: Together, these findings indicate that H3 K27M-mutant DMG represents a heterogeneous disease with regard to outcomes, sites of origin, and molecular pathogenesis in adults versus children.